(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article describes the development of media space in the era of globalization, the increase in information attacks and how this affects the life of society. Crimes committed in cyberspace, in which widely disseminated ideologies, harmful ideas are expressed in the national interests of states, social institutions in society, inviolability of individuals, and moral damage are indicated by specific facts and statistics. What measures the states take to maintain cybersecurity, the laws adopted are mentioned.